2022
DOI: 10.1037/fam0000969
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent caregiving for family: Emotional, social, physical, and academic risk and individual differences.

Abstract: In the United States, it is estimated that more than 5.4 million children and adolescents under age 18 provide care for adult family members who are aging or have a chronic illness, disability, or other health conditions that require assistance. However, little is known about how providing care to the family during childhood and adolescence impacts youth development. We examined whether caregiving as a youth is associated with emotional challenges, peer difficulties, course grades, and physical health risk beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…These racial and ethnic disparities in youths’ experiences providing care are largely consistent with prior research. In Florida, Latinx and Black youth provided higher levels of caregiving compared to youth from White non-Latinx, Asian, or other/mixed-race backgrounds (Armstrong-Carter et al, 2022). Because that sample was less than 3% Asian and other/mixed race, our larger and more diverse sample offered greater statistical power to detect differences between these groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These racial and ethnic disparities in youths’ experiences providing care are largely consistent with prior research. In Florida, Latinx and Black youth provided higher levels of caregiving compared to youth from White non-Latinx, Asian, or other/mixed-race backgrounds (Armstrong-Carter et al, 2022). Because that sample was less than 3% Asian and other/mixed race, our larger and more diverse sample offered greater statistical power to detect differences between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few studies have revealed gender and age differences in students’ experiences of providing caregiving for the family. In the Florida study, boys and younger children provided more caregiving compared to older children and girls, contrasting societal stereotypes of girls and older individuals as caretakers (Armstrong-Carter et al, 2022). In other research, girls and older adolescents more frequently completed household chores compared with boys and younger children (Armstrong-Carter & Telzer, 2021; Telzer & Fuligni, 2009b; Tsai et al, 2013).…”
Section: Differences In Caregiving By Race Ethnicity Gender and Agementioning
confidence: 99%
See 3 more Smart Citations